2014
DOI: 10.1038/ejcn.2014.186
|View full text |Cite
|
Sign up to set email alerts
|

Quality and safety impact on the provision of parenteral nutrition through introduction of a nutrition support team

Abstract: Introduction of an NST increased both the total PN use and the percentage of referrals where enteral nutrition could replace PN. Medical specialty influenced the referral pattern and the likelihood that a referral resulted in PN being initiated. Safety of PN catheters improved significantly following NST introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…A robust aseptic care protocol for patients with intestinal failure (IF) is mandatory to minimize CRBSI or CVT, which threaten sustainable venous access. Dedicated patient‐centered teams, supported by clear protocols, lower catheter complications and possibly the overall costs of care 24 28 . The key to a successful HPN catheter care program is nursing staff with extensive experience of HPN provision alongside a robust patient training program to enable self‐care and supported by a well‐resourced multidisciplinary team, including medical doctors with an interest in IF, dietitians, and clinical pharmacists.…”
Section: Prevention Of Catheter‐related Complications: Catheter Carementioning
confidence: 99%
“…A robust aseptic care protocol for patients with intestinal failure (IF) is mandatory to minimize CRBSI or CVT, which threaten sustainable venous access. Dedicated patient‐centered teams, supported by clear protocols, lower catheter complications and possibly the overall costs of care 24 28 . The key to a successful HPN catheter care program is nursing staff with extensive experience of HPN provision alongside a robust patient training program to enable self‐care and supported by a well‐resourced multidisciplinary team, including medical doctors with an interest in IF, dietitians, and clinical pharmacists.…”
Section: Prevention Of Catheter‐related Complications: Catheter Carementioning
confidence: 99%
“…While a UK IFU has recently reported inpatient CRBSI rate of 0.04/1000 catheter days for new patients admitted to the unit over a 7-year period (over a total of 23 548 inpatient catheter days), it is apparent that the CRBSI rate can be much higher when patients are managed on general medical and surgical wards; for example, CRBSI rates of 5.1 per 1000 catheter days have been noted on medical-surgical ICUs, 5.8 per 1000 for trauma ICUs and 30.2 per 1000 for burn units 32 33. In the general surgical and medical ward setting, CRBSI rates have also been shown to vary, with some studies reporting rates as high as 20.5 per 1000 catheter days 34–36. Clearly, the type of line and clinical setting has a large impact on recorded CRBSI rates.…”
Section: Prevention Of Crbsismentioning
confidence: 99%
“…However, systems aimed at a systematic and coordinated approach to CVC care by all nurses handling CVCs for PN on any wards can improve outcomes throughout the hospital. Indeed, a recent study demonstrated a sustained reduction of CRBSI rates from 6.8 to 0.7 per 1000 catheter days on all general hospital wards outside of a dedicated IFU; this was achieved following the introduction of a nutrition support team that introduced measures including an intravenous access team to site dedicated and appropriate CVCs for PN, alongside training of all ward staff in aseptic procedures 35. Thus, it may be reasonable for all nutrition support teams to set an inpatient CRBSI target of less than 1 per 1000 catheter days, by using quality improvement techniques to share best practice.…”
Section: Prevention Of Crbsismentioning
confidence: 99%
“…It is used when enteral feeding is not possible or only partially possible to meet nutrition requirements. PN is associated with significant risks, including infections, metabolic and nutritional imbalances, reduction of gut integrity and fatality 1-3 ; with reported rates of infection reaching up to 40% of PN patients 4 . This form of therapy also attracts a higher cost than enteral methods, with the cost of PN solution bags ranging between $100 and $380 at the hospital site.…”
Section: Inflammatory Bowel Disease -Basicmentioning
confidence: 99%
“…The search resulted in six articles, of which four were selected. 4,5,6,7 Allocation concealment, intention-to-treat analysis, completeness of follow-up and blinding of investigators, participants and outcome assessors were independently analyzed by three authors and was critically appraised with regards to methods of minimizing selection bias, performance bias, exclusion bias and detection bias. Trial results were combined under a random-effects model.…”
mentioning
confidence: 99%